2020
DOI: 10.1016/j.jretconser.2019.101954
|View full text |Cite
|
Sign up to set email alerts
|

Canal boat tourism: Application of complexity theory

Abstract: This study applies complexity theory to explain how a cognitive-affective model indicates canal boat tour participants' desired behaviour. An in-situ survey was administered to collect data from 202 boat tour participants following a tour of the Canal du Faux-Rempart in Strasbourg, France. The study applies an asymmetrical analysis to investigate the cognitiveaffective factors deriving participants' intentions to recommend canal boat tours. This study uses an asymmetrical approach to explore causal recipes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 90 publications
0
35
0
Order By: Relevance
“…Thus, demographic variables were used in combinations with host and accommodation place attributes in order to describe disabled tourists' behavioral outcomes in relation to p2p accommodations [37]. They were also included in an asymmetrical analysis related to the recommendation intention of canal boat tour participants [38], as well as in a configurational model developed for "predicting residents' support for tourism development (RSTD)" [39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, demographic variables were used in combinations with host and accommodation place attributes in order to describe disabled tourists' behavioral outcomes in relation to p2p accommodations [37]. They were also included in an asymmetrical analysis related to the recommendation intention of canal boat tour participants [38], as well as in a configurational model developed for "predicting residents' support for tourism development (RSTD)" [39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant studies have argued that positive emotional responses during a tour such as satisfaction and pleasure (Hosany and Gilbert, 2010), play a vital role in creating memorable experiences for tourists (Mehran and Olya, 2020; Tung and Ritchie, 2011). More recent studies suggest that tourists’ emotions have an extensive impact on their travel experience (Hosany et al, 2016a, 2016b; Prayag et al, 2015; Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between expected and perceived quality has previously been studied in publications about different economic sectors such as nursing [110] or air transport [111]. In the tourism sector, studies have been carried out into the management of tourist boats [112] and luxury hotels [113]. Most of these studies have shown how the evaluation of the tourist experience at a site is essential to gain knowledge about expected and perceived quality and value.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Hypothesis 2 was also confirmed and shows that the expected quality of a destination directly influences its perceived quality. A high level of expected quality is expected to have a positive effect on the value given by tourists for perceived quality [111,112]. Expected and perceived quality are the basic requirements for any successful tourist destination.…”
Section: Discussionmentioning
confidence: 99%